Feelin' Real/Unbroken: Imagining Blackqueer Education Through Autopoetic Inquiry. Issue 2 (August 2021) - Callier, Durell M.
This autopoetic inquiry offers insights into and critiques of public education. The author specifically interrogates the absence of curricula, which focuses on the fullness of Black LGBTQ+ representation. Through the usage of pivotal artists, lyrics, poetry, and reflection, the author centers a Blackqueer analysis to argue for a reparative educational experience for Black LGBTQ+ youth. Mirrored within the essay is the reality that Black and queer individuals must exhume Black and queer histories, ancestors, and community across the curriculum for ourselves. Likewise, educational practitioners and those who profess to love Black and queer youth must create curricula that represent the totality of Black and queer pasts and present.